2014
DOI: 10.5964/psyct.v7i2.113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality on Perception of Psychological Contract Breach

Abstract: The present research aimed to investigate the influence of personality (Five-Factor Model) on Psychological Contract Breach. Using random sampling procedure, data were collected from 90 faculties of colleges of Royal University of Bhutan. Personality scales by John, Naumann, and Soto (2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…There is a clear focus on the employment relationship between employee employer whereby the employee expects that their psychological contract is different from traditional contracts [36]. It provides the opportunity to explore the processes and content of employment [37]. It influences the behavior of both parties, it is more contractual, expectations have a more generic meaning [7], and it is an important element in any employment relationship [38].…”
Section: Psychological Contractmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear focus on the employment relationship between employee employer whereby the employee expects that their psychological contract is different from traditional contracts [36]. It provides the opportunity to explore the processes and content of employment [37]. It influences the behavior of both parties, it is more contractual, expectations have a more generic meaning [7], and it is an important element in any employment relationship [38].…”
Section: Psychological Contractmentioning
confidence: 99%
“…In a study about the perception of the relationship between age and the breakdown of the psychological contract by the academics Alcover & Martínez-Inigo (2012) [51], they mentioned that breach of psychological contract perceived by workers above 50 age increases compared to individuals younger age. Moreover at the organizational level, the results are decrease in satisfaction and labor welfare, leave intention [35], levels of confidence, especially when the levels of trust between leaders and employees was high [49], low organizational citizenship, increase in volunteer labor rotation and bad or poor relationships [7] are just some factors affecting directly the breach of psychological contract thereby causing a major impact on the performance of the organization [37].…”
Section: Breach Of the Psychological Contractmentioning
confidence: 99%
“…An experiment by Ho, Weingart, and Rousseau (2004) confirmed neurotics to report stronger negative emotive responses to broken promises but make fewer negative attributions about the party who breached the contract. Only recently, Jafri (2014) found that neuroticism was positively associated with perception of breach among 90 teachers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is widely recognized that organizational citizenship behavior has an important influence on organizational effectiveness, adaptability and efficiency [17]. What's more, prior research found that organizational citizenship behavior was closely linked with job satisfaction and had a positive prediction effect on psychological well-being, it can be said that organizational citizenship behavior is an important explicit indicator of employees' Mental health [18] [19].…”
Section: Psychological Contract Breach and Organizational Citizenshipmentioning
confidence: 99%
“…Many empirical researches proved that psychological contract breach influenced employees' extra-role behavior. Atabay surveyed 122 employees and found that the greater the degree of psychological contract breach reported by employees, the less likely they are to engage in organizational citizenship behavior [17]. Furthermore, the influences of psychological contract breach on the negative behaviors of employees also contain reduced employees' contribution to the organizations and weakened employer-employee relations [20].…”
Section: Psychological Contract Breach and Organizational Citizenshipmentioning
confidence: 99%